Migration Journeys to Israel: Narratives of the Way and their Meaning - BenEzer, Gadi (Jewish Identities in a Changing World, 2019)
In Migration Journeys to Israel, psychologist/anthropologist Gadi BenEzer examines the neglected subject of journeys of migrants and refugees, focusing on the experience and meaning of such journeys for Jews migrating to Israel from around the world during the 20th century.